Anthology of sacred song : celebrated arias selected from oratorios by old and modern composers, Vol. 1 Soprano - SPICKER, Max (G> Schirmer, 1901)
Pentecost cantatanMy Spirit was in heavinessnEngedinSt. PeternDestruction of Jerusalem